Pemahaman Konsep Mekanika: Menentukan Arah Percepatan Pendulum, Sulitkah? - Diana Eka Saputri; Muhammad Reyza Arief Taqwa; Fitria Nur Aini; Muhammad Ibnu Shodiqin; Lugy Rivaldo (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This article discusses to reveal students' conceptual understanding in determining the direction of acceleration in two-dimensional movements, with special cases of pendulum motion. To achieve this goal, there are 3 reasoned multiple choice questions which are part of 20 conceptual kinematics questions. The study was conducted on 37 first year physics education master students at Universitas Negeri Malang. This research is quantitative descriptive. Research data shows that students' understanding is still low, only 4 (10.81%) students answer the first question correctly, 3 (8.11%) students answer the second question correctly, and 24 (64%) students answer question correctly. Based on the answer analysis, students are indicated due experience errors, such as (1) the acceleration of the object is always in the direction of motion, (2) at the highest point the object pauses, accelerates zero, and (3) the pendulum had zero acceleration in lowest position because the velocity is maximum.